2014
DOI: 10.3389/fphy.2014.00021
|View full text |Cite
|
Sign up to set email alerts
|

Fracture networks in sea ice

Abstract: Fracturing and refreezing of sea ice in the Kara sea are investigated using complex network analysis. By going to the dual network, where the fractures are nodes and their intersections links, we gain access to topological features which are easy to measure and hence compare with modeled networks. Resulting network reveal statistical properties of the fracturing process. The dual networks have a broad degree distribution, with a scale-free tail, high clustering and efficiency. The degree-degree correlation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…The analysis of the mechanical DFN model shows disassortative mixing, as shown in Tables 1, 2, indicating that the limitations on fracture propagation have a significant impact on the degree mixing. This is consistent with a previous study of fractures in sea ice by Vevatne et al where it was shown that a simple growing fracture network model could produce disassortative mixing if existing fractures could stop the propagation of fractures growing into them [39]. In the model by Vevatne et al the fractures ability to arrest intersecting fractures was a fixed probability, equal for all fractures [39].…”
Section: The Mechanical (M) Model Is Compared For the Competitive (C)supporting
confidence: 80%
“…The analysis of the mechanical DFN model shows disassortative mixing, as shown in Tables 1, 2, indicating that the limitations on fracture propagation have a significant impact on the degree mixing. This is consistent with a previous study of fractures in sea ice by Vevatne et al where it was shown that a simple growing fracture network model could produce disassortative mixing if existing fractures could stop the propagation of fractures growing into them [39]. In the model by Vevatne et al the fractures ability to arrest intersecting fractures was a fixed probability, equal for all fractures [39].…”
Section: The Mechanical (M) Model Is Compared For the Competitive (C)supporting
confidence: 80%
“…Previous studies of two-dimensional fracture networks have shown a strong connection between fracture size and the degree of the corresponding node [8,23]. This follows from the chance of connecting with other fractures increases with the size of the fractures.…”
Section: Resultsmentioning
confidence: 86%
“…Prominent contributions to a systematic understanding and modelling of our Planet have been provided by the analysis of satellite observations. [3][4][5][6][7][8] Motivated by such general observation and the underlying theoretical concepts, the present investigation is thus addressed to identify characteristic patterns and quantify the structure and dynamics of image sets acquired by the LANDSAT Thematic Mapper (TM) satellite in different locations worldwide with the general purpose to obtain meaningful indicators for assessing ecosystem organization, dynamics, stability, and functions of key relevance to the sustainable management of natural resources, social organizations and technological infrastructures.…”
Section: Introductionmentioning
confidence: 99%